Improving Access to Justice for the Community in Reaching the Pekanbaru State Administrative Court Building Based on Regulation of the Supreme Court of the Republic of Indonesia Number 1 of 2014 (Prosiding Keislaman dan Sains, 2025)
The purpose of this study is to determine the improvement in access to justice for people who have difficulty reaching the Pekanbaru State Administrative Court building based on the Regulation of the Supreme Court of the Republic of Indonesia Number 1 of 2014 concerning Guidelines for the Provision of Legal Services for the Underprivileged in the Court. This research will look at the implementation of the regulation and provide input for improving legal aid services at the Pekanbaru PTUN in particular. Geographical and economic constraints, Many people in the Regency and rural areas have difficulty reaching the Pekanbaru PTUN building due to distance, transportation costs, or financial limitations. Role of Perma No. 1 of 2014 This regulation is designed to provide more inclusive legal services to the underprivileged, including in the state administrative court. Purpose of Perma No. 1 of 2014 Ensure that every individual, without exception, has equal access to justice. The limitation of this research is that this research is only conducted in the scope of Riau Province in accordance with the jurisdiction of Riau PTUN. Thus, the research will only have implications for Riau Province, especially for the people of Riau Province who need legal assistance. The results of this study indicate that there is a need to improve access to the Riau PTUN building for underprivileged people using legal aid instruments. In addition, there is also a need to increase the use of e-court if it is not possible at all for people living in remote areas to access the PTUN building directly. Amendments to the Regulation of the Supreme Court of the Republic of Indonesia Number 1 of 2014 concerning Guidelines for the Provision of Legal Services for the Underprivileged in Court need to be made for this matter.
Keywords: Justice; Legal Aid Services; Access to Justice; Improvement; Pekanbaru State Administrative Court